Student leadership model for Hispanic serving and emerging Hispanic serving institutions - Guerra, Norma S.; Loera, Daniel; Enciso, Martha; Claeys, Lorena (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Although empirical evidence indicates that HSIs (Hispanic Serving Institutions) are making some progress in recognizing that enhancing the racial and cultural experiences of Latino/a/x students, "Latinx-enhancing" is part of their role as institutions that enroll and serve large numbers of minoritize students (Garcia, 2019), there are still institutional gaps on prioritizing opportunities for Latino/a/x students to engage in leadership development. Latino/a/x students often rely on informal out-of-college support systems found in their community-- comunidad, such as family and peers to thrive within college (Ceballo, 2004; Easley, et al, 2012), it is important to assist them in their development and implementation of strengths-based problem-solving communication approach (Guerra, 2015, 2016)"--